NON-OBSERVANCE OF MAXIMS IN FACEBOOK CONVERSATION FROM GENDER PERSPECTIVE: A Case Study of the Ninth Semester of English Students at One University in Bandung - Hanifah, Irma Rizkiani (2013)
This study was aimed at investigating types of maxims which are not observed by male and female users and how male and female users fail to observe a maxim in their conversation. This study involved 16 male and 15 female Facebook users of students majoring in English at one university in Bandung. This study applied qualitative case study method. The data were in the form of conversations in Facebook that were downloaded from August 2012 until December 2012. The data were collected through several considerations of non-observance of maxims within the conversation based on Grice's theory of conversational implicature. There were several procedures in analyzing the data: identifying, classifying, calculating, and interpreting. The findings showed that male users commonly failed to observe the maxim of relation by giving irrelevant contribution, while female users commonly failed to observe the maxim of quantity by giving more information. In addition, flouting of maxim is the most frequent non-observance of maxim that was performed by both male and female users in their conversation. Thus, both users tended to make a joke, to stay close with friends, or just to contribute the conversation when they performed such non-observance of maxims. Keywords: Non-observance of Maxims, Facebook, Conversation, Gender, Cooperative Principle, Implicature. Penelitian ini bertujuan untuk mencari tahu macam-macam maxim apa saja yang gagal diamati oleh para pengguna Facebook baik pria maupun wanita dalam percakapannya. Penelitian ini melibatkan 16 pengguna Facebook pria dan 15 pengguna Facebook wanita dari murid-murid bahasa Inggris di satu perguruan tinggi di Bandung. Penelitian ini menggunakan metode kualitatif studi kasus. Data penelitian ini berupa percakapan dalam Facebook yang diunduh dari Agustus hingga Desember 2012. Data penelitian dikumpulkan melalui beberapa pertimbangan dalam pelanggaran maxim-maxim di dalam percakapan berdasarkan teori Grice mengenai implikatur dalam percakapan. Terdapat beberapa prosedur dalam menganalisa data penelitian ini: mengidentifikasi, mengklasifikasi, menghitung, dan mentafsirkan. Hasil dari penelitian ini menunjukkan bahwa para pengguna pria cenderung melanggar relation maxim dengan memberikan kontribusi yang tidak relevan, sementara pengguna wanita cenderung melanggar quantity maxim dengan memberikan informasi yang berlebih. Sebagai tambahan, flouting maxim ditemukan sebagai pelanggaran maxim yang paling banyak dilakukan oleh para pengguna baik pria maupun wanita. Dapat disimpulkan bahwa para pengguna cenderung menyiratkan suatu lelucon, menyiratkan keingingan tetap berkomunikasi dengan teman , atau hanya ingin berkontribusi di dalam percakapan ketika mereka melakukan pelanggaran maxim-maxim tersebut. Kata-kata kunci: Pelanggaran maxim-maxim, Facebook, Percakapan, Prinsip Kooperatif, Implikatur.